Novel Modified High Step-Up DC/DC Converters with Reduced Switch Voltage Stress - Lingling Liu; Donghui Li (International Transactions on Electrical Energy Systems)
This paper presents the improved switched inductor unit and new step-up DC/DC converters with reduced switch voltage stress and high voltage gain. The proposed switching-inductor unit is composed of 1 switch, 2 diodes, and 2 inductors, which can realize the step-up function. Through comparison, the better topology is selected from the proposed converters, which is named the double-switch high step-up (DS-HS) converter. The CCM operating principles and voltage gain of the DS-HS converter are analyzed. Then, the influences of nonideal components, efficiency analysis, small signal modeling and control, and design criteria of components are discussed. The comparison of the converters is given, and the loss of the DS-HS converter is lower through theoretical derivation, which shows that the DS-HS converter has the advantages of high voltage gain, low voltage stress, and high efficiency. Finally, in order to verify the effectiveness of the DS-HS converter, simulation and experimental results are given, and the efficiency of the DS-HS converter can reach 96.15%.